2022
DOI: 10.1007/s10875-022-01296-4
|View full text |Cite
|
Sign up to set email alerts
|

Defining Clinical and Immunological Predictors of Poor Immune Responses to COVID-19 mRNA Vaccines in Patients with Primary Antibody Deficiency

Abstract: Immune responses to coronavirus disease 2019 (COVID-19) mRNA vaccines in primary antibody deficiencies (PADs) are largely unknown. We investigated antibody and CD4 + T-cell responses specific for SARS-CoV-2 spike protein (S) before and after vaccination and associations between vaccine response and patients' clinical and immunological characteristics in PADs. The PAD cohort consisted of common variable immune deficiency (CVID) and other PADs, not meeting the criteria for CVID diagnosis (oPADs). Anti-S IgG, IgA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…The results are consistent with a previously reported expansion of the T-cell memory subsets in patients with IEI and healthy controls 28 days after vaccination with the BNT162b2 mRNA vaccine [ 28 ]. However, a recent study examining immunological predictors of impaired immune response to SARS-CoV-2 vaccination found no association to central memory CD4+ or CD8+ T cells, but a significantly higher frequency of effector memory CD8+ T cells in those of impaired humoral immune response [ 36 ], and a similar trend has also been observed with humoral response to influenzae vaccination in CVID patients [ 55 ]. We found no significant relationship between long-term anti-spike humoral response and B-cell subsets, consistent with reports on early vaccination responses in IEI patients where there was no variation in the B-cell compartment a month after vaccination was reported [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The results are consistent with a previously reported expansion of the T-cell memory subsets in patients with IEI and healthy controls 28 days after vaccination with the BNT162b2 mRNA vaccine [ 28 ]. However, a recent study examining immunological predictors of impaired immune response to SARS-CoV-2 vaccination found no association to central memory CD4+ or CD8+ T cells, but a significantly higher frequency of effector memory CD8+ T cells in those of impaired humoral immune response [ 36 ], and a similar trend has also been observed with humoral response to influenzae vaccination in CVID patients [ 55 ]. We found no significant relationship between long-term anti-spike humoral response and B-cell subsets, consistent with reports on early vaccination responses in IEI patients where there was no variation in the B-cell compartment a month after vaccination was reported [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Primary antibody deficiency patients with a history of autoimmunity have previously been reported to have a poorer response to vaccination [ 36 ]. In this study, we were not able to identify an association between the magnitude of the immune response and clinical manifestations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More importantly, the detection of specific antibodies after COVID-19 vaccination raises important questions on the quality and longevity of the humoral immune response, since the seroconversion state has potential clinical implications for treatment in SARS-CoV-2-infected CVID patients. Functional assessments of humoral immunity already revealed that CVID patients express lower neutralizing antibody levels than healthy individuals [ 8 11 , 15 ]. Avidity of generated antibodies was analyzed in two recent studies, reporting similar levels of antibody avidity in CVID patients and healthy individuals 4 weeks after second COVID-19 vaccination but without significant increase after more than two vaccinations [ 9 , 16 ].…”
Section: Introductionmentioning
confidence: 99%